An empirical study on the factors influencing mobile library usage in IoT era. Issue 4 (3rd October 2018) - Wang, Xiwei; Li, Jiaxing; Yang, Mengqing; Chen, Yong; Xu, Xiaobo
Abstract : Purpose: The purpose of this paper is to construct an information ecology factor-TAM model to explore how information, people, and information environment impact mobile library users' behavioral intention. Design/methodology/approach: An empirical study based on an information ecology factor-TAM model. Findings: The results of model test indicate that information, people, and information environment affect users' behavioral intention to use mobile library in the information ecology environment. This paper provides a new theoretical perspective to understand users' behavior of mobile library. It also provides practical guidelines to promote the usage of mobile library. Originality/value: Internet of Things makes digital library one important channel for people to obtain information. Mobile internet makes it possible to access a variety of information anytime and anywhere. With the rapid grow of the number of mobile internet users, the usage of mobile library does not grow correspondingly. This paper explores the reasons.